Selection on Human Genes as Revealed by Comparisons to Chimpanzee cDNA - Hellmann, Ines; Zöllner, Sebastian; Enard, Wolfgang; Ebersberger, Ingo; Nickel, Birgit; Pääbo, Svante (Genome Research, 2003)
To better understand the evolutionary forces that affect human genes, we sequenced 5055 expressed sequence tags from the chimpanzee and compared them to their human counterparts. In conjunction with intergenic chimpanzee DNA sequences and data on human single-nucleotide polymorphisms in the genes studied, this allows us to gauge the extent to which selection affects human genes at a genome-wide scale. The comparison to intergenic DNA sequences indicates that about 39% of silent sites in protein-coding regions are deleterious and subject to negative selection. Further, when the divergence between human and chimpanzee is compared with the extent of nucleotide polymorphisms among humans in the same sequences, there is significantly higher divergence in the 5′ untranslated regions (UTRs) but not in other parts of the transcript. This indicates that positive selection may have had a considerable influence on 5′UTRs. The dinucleotide CG (CpG) also exhibits a different substitution pattern within 5′UTRs as compared with other parts of the genome.